Effect of stellate ganglion block on perioperative myocardial injury following thoracoscopic surgery for lung cancer (SGBMI): protocol for a single-centre, randomised controlled trial - Yang Liu; Wei Wu; Hong Shi; Haofei Dai; Meiyun Liu (BMJ Open Respiratory Research)
Introduction Myocardial injury is a common complication of thoracoscopic surgery. The stellate ganglion block is believed to affect myocardial oxygen consumption. The Stellate Ganglion Block and Myocardial Injury (SGBMI) trial aims to test the hypothesis that stellate ganglion block can reduce the incidence of perioperative myocardial injury in patients undergoing thoracoscopic surgery for lung cancer.Methods and analysis The SGBMI trial is a double-blind, randomised trial comparing the effects of a stellate ganglion block and a sham procedure in patients with cardiovascular risk factors undergoing thoracoscopic surgery. The exclusion criteria include procedure-related contraindications and severe heart failure. The stellate ganglion block or sham procedures will be performed preoperatively. The primary outcome is myocardial injury within 30 days of the follow-up. The main safety outcomes are sepsis, infection and procedure-related complications. We will enrol 248 patients to ensure at least 80% power for the evaluation of the primary outcome. The primary results of the SGBMI trial are expected to be announced by the year 2027.Ethics and dissemination Ethical approval for the study is obtained from the Ethics Committee of the Shanghai Pulmonary Hospital (approval number: L22-394). Written informed consent will be obtained from all participating patients. The publication of results in a peer-reviewed journal and presentations at conferences are anticipated.Trial registration number ChiCTR2300071469 (registered on 16 May 2023).